# Answer to Question #6282 in Abstract Algebra for Nguyen

Question #6282

1/2m-3=5/6-2/3m

Expert's answer

1/(2m-3)=5/6-2/3m

1/(2m-3)+2/3m=5/6

(3m+4m-6)/(3m*(2m-3))=5/6

Note that m<>3/2 and m<>0

42m-36=15m(2m-3)=30m^2-45m

30m^2-87m+36=0

D=87^2-4*30*36=57^2

m1=(87+57)/60=144/60=72/30=36/15=12/5

m2=(87-57)/60=1/2

1/(2m-3)+2/3m=5/6

(3m+4m-6)/(3m*(2m-3))=5/6

Note that m<>3/2 and m<>0

42m-36=15m(2m-3)=30m^2-45m

30m^2-87m+36=0

D=87^2-4*30*36=57^2

m1=(87+57)/60=144/60=72/30=36/15=12/5

m2=(87-57)/60=1/2

## Comments

## Leave a comment